Synthesis and preliminary evaluation of brominated 5-methyl-2,4-dihydropyrazol-3-one and its derivatives as cytotoxic agents - Khan, Rahat; Uddin, Md. Imam; Alam, Md. Sultan; Hossain, Mohammad Mamun; Islam, Md. Rabiul (Bangladesh Journal of Pharmacology, 2008)
Derivatives of 5-Methyl-2,4-dihydro-pyrazol-3-one (1a), 5-Methyl-2-phenyl-2,4-dihydro-pyrazol-3-one (1b) and 2-(2,4-Dinitro-phenyl)-5-methyl-2,4-dihydro-pyrazol-3-one (1c) have been brominated in various ways. The compounds (1a, 1b, 1c) were synthesized by condensation reaction between the ethylacetoacetate and hydrazine derivatives. All the products have been characterized by extensive use of IR, 1H-NMR, 13C-NMR and Mass spectral analysis. Investigation of the cytotoxicity of these compounds was carried out against brine shrimp by lethality bioassay. The cytotoxicity studies of the synthesized compounds revealed that compound 4,4-Dibromo-2-(2,4-dinitro-phenyl) -5-methyl -2,4-dihydro-pyrazol-3-one (2c) had shown tremendous bioactivity against brine shrimp. However, the Compounds 4,4-dibromo-5-methyl-2,4-dihydro-pyrazol-3-one (2a), 4,4-Dibromo-2-(2,4-dibromo-phenyl)-5-methyl-2,4-dihydro-pyrazol-3-one (2b) and 4,4-dibromo-2-(dinitro-phenyl)-5-methyl-2,4-dihydro-pyrazol-3-one (2c) showed higher activity leaving the other compounds all most inactive.